Do Banks Conduct Earnings Management Prior to Seasoned Equity Offerings to Meet Capital Adequacy Regulation? - Ricky Karunia Lubis; Risky Ainur Hardianti; Rizky Darmawan; Amrie Firmansyah (The Indonesian Journal of Accounting Research, 2023)
The episodic financial crises in Indonesia highlighted the importance of strengthening banks’ capital to maintain financial stability. To achieve such an objective, the Financial Service Authority (OJK) issued OJK Regulation Number 12/2020, which mandates banks to meet capital standards to preserve a sound financial system. However, given the short timeframe, banks need to conduct seasoned equity offerings (SEOs) to satisfy the regulation, where they could potentially perform earnings management before the SEOs to raise optimal capital. We used secondary data derived from www.idx.co.id from Q1-2019 to Q4-2021. We use the Wilcoxon signed-rank test to examine whether there are significant abnormal LLPs between pre- (2019-2020) and post-regulation (2020-2021), suggesting that bank managers conduct earnings management before SEOs through their discretion over LLP items. We also use a correlation test to investigate the association between earnings management and LLPs. Our study finds that bank managers engage in earnings management before SEOs to meet the capital adequacy regulation, given the short timeframe from the regulator. We also find a strong correlation between earnings management and LLPs. The study results suggest that bank managers engage in earnings management, regardless of whether it is income-increasing or income-decreasing, before the SEO period in response to the capital adequacy regulation through their use of discretion over LLP items.